Wear of nanohybrid and microfilled composite resin in occlusal restoration of first permanent molar tooth (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This study compared the wear of nanohybrid and microfilled composite restorative material in occlusal restoration of first permanent molar tooth. In total, 60 first permanent molar teeth having carious lesion without any clinical and radiological indication of pulpal involvement, removal of carious dental hard tissues was performed using round carbide bur and a class I cavity was prepared, rinsed with water and then dried with gentle air. These cavities were filled with either nanohybrid or microfilled composite resin by simple random sampling by lottery method. All teeth were subjected to clinical qualitative and quantitative wear test at baseline, 3, 6 and 9 months observation period. The quantitative wear was analyzed by profile meter. The results showed that the wear depth of microfilled was significant than the nanofilled composite resin. It can be concluded that quantitative wear of microfilled had greater wear than that of nanohybrid composite restorations.